Effect of 1.5% potassium oxalate on sensitivity control, color change, and quality of life after at-home tooth whitening: A randomized, placebo-controlled clinical trial - Barros, Antonia Patricia Oliveira; da Silva Pompeu, Danielle; Takeuchi, Elma Vieira; de Melo Alencar, Cristiane [UNESP]; Alves, Eliane Bemerguy; Silva, Cecy Martins (Public Library of Science (PLoS), 2022)
Objective This clinical trial evaluated the effect of 1.5% potassium oxalate (PO) in controlling sensitivity and color change after at-home tooth whitening. It also evaluated the influence of PO on health-related quality of life (HRQoL) and the degree of patient satisfaction after bleaching treatment. Materials and methods Fifty volunteers were randomized into two groups (n = 25): At-home bleaching gel with 22% carbamide peroxide for 45 min + placebo gel (GP) or 1.5% PO (GPO) for 10 min. The intensity of tooth sensitivity was assessed daily through the visual analog scale. The color analysis was performed three times: baseline, 21 days, and 1 month after the last application of the whitening gel. The impact of the oral condition on the patient’s quality of life (OIDP) was used to measure the impact caused by the whitening treatment in relation to the individuals’ ability to carry out their daily activities and its influence on HRQOL. Results No difference in tooth sensitivity was observed (p > 0.05). In addition, there was no difference in color change between groups (p > 0.05). However, there was an intragroup statistical difference throughout the evaluation period (p <0.05). The OIDP analysis showed a statistical difference between the groups (p > 0.05) and there was no difference between the groups regarding the degree of satisfaction with the bleaching (p > 0.05). Conclusions The 1.5% PO was effective in preventing sensitivity and did not interfere with tooth whitening. Desensitizing therapy had a positive impact on quality of life and patient satisfaction.